A composite controller based on nonlinear H_∞ and nonlinear disturbance observer for attitude stabilization of a flying robot - Vahid Razmavar; Heidar Ali Talebi; Farzaneh Abdollahi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In this article a novel composite control technique is introduced. We added a nonlinear disturbance observer to a nonlinear H_∞ control to form this composite controller. The quadrotor kinematics and dynamics is formulated using euler angles and parameters. After that, this nonlinear robust controller is developed for this flying robot attitude control for the outdoor conditions. Because under these conditions the flying robot, experiences both external disturbance and parametric uncertainty. Stability analysis is also presented to show the global asymptotical stability using a Lyapunov function. The simulation results showed that the suggested composite controller had a better performance in comparison with a nonlinear H_∞ control scheme.